2014
DOI: 10.1007/s12017-014-8298-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of Multiple Sclerosis: An Updated Review

Abstract: Multiple sclerosis (MS) is an inflammatory and neurodegenerative disease characterized with autoimmune response against myelin proteins and progressive axonal loss. The heterogeneity of the clinical course and low concordance rates in monozygotic twins have indicated the involvement of complex heritable and environmental factors in MS pathogenesis. MS is more often transmitted to the next generation by mothers than fathers suggesting an epigenetic influence. One of the possible reasons of this parent-of-origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 122 publications
2
46
0
3
Order By: Relevance
“…Indeed, we cannot exclude the fact that the global methylation pattern in different abnormalities/diseases might future determinate the initial symptoms of ailing humans. In addition, the results of the methylation analysis for selected genes showed that the inheritance of affected DNA methylation patterns is a likely etiological candidate for many heritable disorders that were previously considered idiopathic 48495051…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we cannot exclude the fact that the global methylation pattern in different abnormalities/diseases might future determinate the initial symptoms of ailing humans. In addition, the results of the methylation analysis for selected genes showed that the inheritance of affected DNA methylation patterns is a likely etiological candidate for many heritable disorders that were previously considered idiopathic 48495051…”
Section: Discussionmentioning
confidence: 99%
“…Genetic risk MS is a complex disease involving interactions between environmental and genetic factors, with epigenetic mechanisms likely involved [Harbo et al 2013;Küçükali et al 2015]. Patients are concerned about risk to their children.…”
Section: Female Versus Male Patientsmentioning
confidence: 99%
“…Various genetic, immunological and environmental factors have been associated with inducing the onset and progression of the disease (1)(2)(3). Genetics may play a role in the disease pathogenesis as MS is more common in the Caucasian population and the frequency of MS appears to increase with the distance from the Equator in the two hemispheres (4).…”
Section: Introductionmentioning
confidence: 99%